Characterization in children aged 4 to 6 years with dental interference from children's daycare institutions - Hechavarría Martínez, Bárbara Olaydis (2020)
Objective: the objective of characterizing children from 4 to 6 years of age from nursery schools in the health area of the "Julián Grimau García" Teaching Polyclinic in Santiago de Cuba, according to clinical and epidemiological variables.   Materials and methods: An observational, descriptive and cross-sectional study was carried out in children from 4 to 6 years of age belonging to the nursery circles of the health area of the "Julián Grimau García" Teaching Polyclinic in Santiago de Cuba, in the period of July 2016 to April 2017 .The study was constituted by the 57 children from 4 to 6 years of age belonging to the 2 children's circles of the aforementioned health area, of both sexes and who presented dental interferences. To obtain the data, a structured interview was conducted with parents or guardians, in order to obtain accurate and verified data, using the percentage as a summary measure. The oral examination was performed on children using the tongue depressor and natural or artificial light. Results: the male sex and the period of temporary dentition predominated. Buccal breathing and bottle use were the most practiced deforming habits. Conclusions: Concluding that most of the children examined did not present anomalies of the occlusion. Considering this, we recommend carrying out analytical studies in the area that allow deepening the study of dental interferences in children as a causal factor of malocclusions, elevating health promotion and prevention activities to pregnant women and mothers on the importance of practicing favorable lifestyles for the health and development of the stomatognathic system of their children from an early age.